Determining the Effect of Various Sowing Dates on Yield and Yield Components of Chickpea (Cicer arietinum L.) Varieties in Ethiopia - Getachew, Adinew; Abraham, Thomas (Emerging Issues in Agricultural Sciences Vol. 3, 2023)
The present study determining the effect of Various Sowing Dates on Yield and Yield Components of Chickpea (Cicer arietinum L.) Varieties. Chickpea (Cicer arietinum L.) is the second most important pulse crop globally, after common bean (Phaseolus vulgaris). It delivers benefits to farming systems that range from a smaller carbon footprint due to biological nitrogen fixation to improved soil health. A field experiment was conducted at Toke Kutaye District in Nega-file kebele on farmer’s field during September, 2019 to November, 2019 under rain fed conditions of the main cropping season. Treatments consisted of four sowing dates (September 4th, September 14th, September 24th, and October 5th) and four kabuli varieties of chickpea; namely Dube (standard check), Dalota, Teji and Ejere. Among the tested verities, Dalota variety produced the highest grain yield and found suitable for Toke Kutaye and similar agro-ecologies. Dalota variety produced the highest number of pods (79.7) per plant. the main effects of sowing date and varieties were significantly different on biological yield. Highest biological yield (3776.9 kg ha-1 and 3761 kg ha-1) were recorded from September 24th and September 14th sown plots, respectively. Among varieties tested, the highest biological yield (3723.8 kg ha-1) was obtained from local variety. Highest grain yield (2415.4 kg ha-1) was recorded from plots sown on September 14th whereas Dalota variety produced highest grain yield (2051.25 kg ha-1). In case of harvest index, highest (67.9% and 59.6%) was recorded from September 14th sown plots and Dalota variety, respectively. It is concluded that among all tested treatments, the Dalota variety and the September 14th sowing date stood out as the best and could be suggested for the production of chickpeas in the study area.